Multiple examinations indicated associations between abnormal regional homogeneity and cognitive dysfunction in major depressive disorder - Wang, Yun; Li, Xiaoling; Yan, Haohao; Zhang, Qinqin; Ou, Yangpan; Wu, Weibin; Shangguan, Webo; Chen, Wensheng; Yu, Yang; Liang, Jiaquan; Wu, Wanting; Liao, Hairong; et al. (Frontiers in Psychology, 2023)
Background: This study aimed to investigate the relationship between regional neural activity and multiple related indicators in patients with major depressive disorder (MDD). Methods: Forty-two patients and 42 healthy controls (HCs) were enrolled. Pearson correlation analyses were applied to examine the associations between abnormal regional homogeneity (ReHo) and different indicators. Support vector machine (SVM) analyses were used to evaluate the effect of abnormal ReHo in differentiating patients from controls. Results: Compared with HCs, patients with MDD had increased ReHo in the left inferior temporal gyrus (ITG) and decreased ReHo values in the left putamen, anterior cingulate cortex (ACC), and precentral gyrus. The ReHo of the left putamen was positively correlated with the PR interval, Repeatable Battery for the Assessment of Neuropsychological Status 4A, and Discriminant analysis (D), and negatively correlated with Ae (block) and Ae (total). The ReHo value of the left ACC was positively correlated with the severity of depression, Stroop Color Word Test of C-2B+100 in reaction time, and negatively correlated with Ce (Missay) and Perseverative Responses. The ReHo of the left ITG was positively correlated with the Neuroticism scores and negatively correlated with the Lie scores. SVM results showed that the ReHo values of the left putamen and left ACC could be used for diagnosis with high accuracy. Conclusions: These results suggested that the decreased ReHo in the salience network could serve as potential imaging biomarkers for diagnosis, and serve as a quantitative indicator of the severity of cognitive symptoms in patients with MDD.